Effect of Eccentric Exercise on Metabolic Health in Diabetes and Obesity - Gergő Szűcs; Márton Pipicz; Márton Richárd Szabó; Tamás Csont; László Török; Csaba Csonka (SpringerOpen, 2023)
Abstract There is a growing body of evidence showing the importance of physical activity against civilization-induced metabolic diseases, including type 2 diabetes (T2DM) and obesity. Eccentric contraction, when skeletal muscles generate force by lengthening, is a unique type of skeletal muscle activity. Eccentric contraction may lead to better power production characteristics of the muscle because eccentric contraction requires less energy and can result in higher tension. Therefore, it is an ideal tool in the rehabilitation program of patients. However, the complex metabolic effect (i.e., fat mass reduction, increased lipid oxidation, improvement in blood lipid profile, and increased insulin sensitivity) of the eccentric contraction alone has scarcely been investigated. This paper aims to review the current literature to provide information on whether eccentric contraction can influence metabolic health and body composition in T2DM or obesity. We also discussed the potential role of myokines in mediating the effects of eccentric exercise. A better understanding of the mechanism of eccentric training and particularly their participation in the regulation of metabolic diseases may widen their possible therapeutic use and, thereby, may support the fight against the leading global risks for mortality in the world.